Intraoperative neuromonitoring ethics and governance - Nel, Jacques David (My University, 2020)
This research report sets out to evaluate the ethics and governance in the field of Intraoperative neuromonitoring (IONM) in South Africa. The purpose of this research report will be to identify the ethical and legal dilemmas that are present when performing IONM without being registered with the Health Professions Council of South Africa (HPCSA). The focus will be on the ethical controversies that arise when performing IONM without registration. Ethical principles such as respect for persons, autonomy, beneficence, non-maleficence and justice will be used to defend my position. There will also be a legal component which will focus on the issues of IONM in the courtroom within South Africa. National and international guidelines and recommendations will be used to defend the regulatory aspect of the argument.In South Africa IONM is practised with a lack of regulatory and ethical policies in place. Performing and interpreting IONM constitutes a medical procedure and so a person wishing to perform IONM must have a particular set of medical skills under the constructs of healthcare. This not only ensures that the person understands and acknowledges ethics and health law within IONM but also allows the person to be regulated by a governing body, the HPCSA. The HPCSA serves as a body to regulate healthcare professionals and allows patients to lay complaints against healthcare professionals if there has been forms of negligence. There is, however, little mention of unregulated persons performing IONM without registration with the HPCSA. Registration with the HPCSA ensures that persons performing IONM understand the function of a healthcare professional while performing IONM. Being registered with the HPCSA also enforces legal responsibility to the person performing IONM. There are currently no guidelines as to the ethical and legal responsibilities of both the surgeon and the person performing the IONM. Furthermore, there is also nodocumented standard of skill that must be expressed by the person performing the IONM. This reveals several ethical and legal dilemmas, for example undermining autonomy and respect for persons and the possibility of harm and diminished benefit.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2020